Nuclear structure - Eisenbud, Leonard; Wigner, Eugene Paul, 1902-1995 (Investigations in physics, 1958)
A clear and well-organized review of what is presently known about nuclear structure. Emphasis is less upon mathematical detail than upon the obtaining of a clear perspective which relates the various lines of approach to this complex and rapidly developing field. Particular attention is paid to nuclear models and to the several types of nuclear reactions. Originally published in 1958. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.